Iatrogenic chorioamniotic separation and septostomy following fetoscopic laser photocoagulation for twin–twin transfusion syndrome. (10th March 2022) - Krispin, E.; Mustafa, H. J.; Sun, R. C.; Donepudi, R.; Espinoza, J.; Nassr, A. A.; Belfort, M. A.; Sanz Cortes, M.; Mostafaei, S.; Harman, C.; Turan, O.; Shamshirsaz, A. A.
ABSTRACT: Objective: To compare the perinatal outcomes of pregnancies complicated by chorioamniotic separation (CAS) vs septostomy following fetoscopic laser photocoagulation (FLP) for twin–twin transfusion syndrome (TTTS). Methods: This was a retrospective cohort analysis of monochorionic diamniotic twin pregnancies with TTTS that underwent FLP at one of two university‐affiliated tertiary medical centers between January 2012 and December 2020. CAS and septostomy were diagnosed either during the procedure or by ultrasonography within 24–48 h after FLP. Data on procedure and postprocedure parameters, pregnancy outcomes and survival were collected from the patients' electronic medical records. Pregnancies were stratified according to the presence of CAS, septostomy or neither. Patients diagnosed with both CAS and septostomy were analyzed separately. Results: Of the 522 women included in the cohort, 38 (7.3%) were diagnosed with CAS, 68 (13.0%) with septostomy and 23 (4.4%) with both CAS and septostomy. The remaining 393 (75.3%) women comprised the control group. Groups did not differ in demographic characteristics. The septostomy group had a lower rate of selective fetal growth restriction than did the CAS and control groups (24.2% vs 36.8% vs 42.7%, respectively; P  = 0.017). Moreover, intertwin size discordance was lower in the septostomy group (15.1% vs 23.4% in the CAS group and 25.5% in the control group; P  = 0.001). Median gestational age at FLP was significantly lower in the CAS group (19.3 weeks vs 20.4 weeks in controls and 20.9 weeks in the septostomy group; P  = 0.049). The rate of delivery prior to 34 weeks was significantly higher in the CAS group (89.2%), followed by the septostomy group (80.9%), compared with the control group (69.0%) ( P  = 0.006). A secondary analysis demonstrated that patients with both CAS and septostomy presented the highest rates of delivery prior to 34 weeks (100%) and 32 weeks (68.2%). Conclusions: CAS and septostomy following laser surgery for TTTS are independently associated with higher rates of preterm delivery. The presence of these two findings in the same patient enhances the risk of prematurity. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.